Hybrid-virtual simulations for Canadian medical students during the COVID-19 pandemic - Reel, Riley M; Gunther, Kevin I; Kirk, Samuel R; Landells, David Graham Oliver; Theilmann, Anne L; Haines, Morgan J (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Implication Statement: Given the efficacy of simulations as a medical education tool, the inability to provide them during the COVID-19 pandemic may be detrimental to pre-clinical medical student learning. We developed hybrid simulations, where remote learner participants could direct an in-person assistant. This offered a learning opportunity that was more realistic than fully virtual simulations and abided by public health guidelines. Hybrid simulations provided an opportunity for medical students to practice real-time clinical decision making in a remote, high-fidelity, simulated environment. This approach could be adapted for rural healthcare students and professionals to participate in simulations without a local simulation centre.